Development of polyethylene/nanoclay masterbatch for use in wood–plastic composites. (May 2013) - Gong, G; Nyström, B; Joffe, R
Abstract : In this work, organoclay reinforced high density polyethylene (HDPE) nanocomposites were prepared at laboratory scale using a batch mixer. Processing conditions, maleic anhydride modified polyethylene (MAPE) type and MAPE/clay weight ratio were optimised. The microstructure of the resultant nanocomposites was analysed by X-ray diffraction and melt rheology tests, and flexural properties and thermal stability were evaluated. Three types of MAPEs with different melt flow indices (MFI) and maleic anhydride contents all improved the interaction between HDPE and clay and promoted clay dispersion. Nanocomposites where the MAPE with MFI most similar to HDPE was used showed the best exfoliation of clay and the strongest HDPE/clay interface. Mechanical properties were slightly improved, while thermal stability was distinctly enhanced in these HDPE nanocomposites compared with neat HDPE and HDPE nanocomposite without MAPE. The prepared HDPE nanocomposites show the potential to improve the thermal stability of wood–plastic composites for structural applications.